An Encounter with Predatory Journal - Maharjan, L.; Shah, A. (Kathmandu University Medical Journal, 2020)
The concept of open access journals was introduced with the aim to make the scientific articles accessible and visible to all. But a new threat called predatory journals has emerged targeting the young researchers of developing nations. These bogus journals mislead the authors as well as readers in various negative ways. Hence, we should recognize such journals and avoid becoming the prey.